The Politeness Principle in the Poetry of Ahmed Matar: A Pragmatics Study - Hassan, Abdulgafar Fatah; Dze Yi, Delkhosh Jarallah (Al-Adab Journal, 2020)
This study deals with one of the principles of speech or conversation, which together with other topics pertainging to it, e.g. face theory and politeness theory, represent key topic in prgamtics. These princilpes are applied to selected poem of the Iraqi poet Ahmad Matar. The study takes an analytical and descriptive approach in analyzing the data of from a pragmatic perspective, so as to identdifiy the peot’s intented meaning and the ligusitics devices he utilized to convey that meaning. The poet used some devices that are similar to the ones used in is regular language and in daily dialogues. He aims to maximize the impact on the recipient and sustain the process of communicating and interacting with his texts. His style is meant to convince others of his political and social ideas and visions.